GEOCHEMICAL SPECIALIZATION OF OCENIC SULFIDE ORES - Krasnov S.G. (My University, 1990)
The ternary diagrams of the composition of the ores presented shows the relationships among the chief metals in the ores of all the ore districts studied in the ocean by 1988. In contrast to the usual practice, the relationships of the concentrations for each area were not computed between the average, but between the maximal values recorded in individual samples of the ore aggregates. Thus for plotting each point on the ternary diagrams, out of the whole number of available analyses for a specific area (from a few to some tens of determinations), we actually used data on no more than three samples, representing the most 'contrasting' ore types. Probably at the present stage of study of oceanic sulfides, when the sampling method (chiefly by means of manned submersibles) does not provide statistically representative data, but instead the ore varieties most typical of each area are studied, such an approach may be justified. The data obtained in this way definitely cannot be directly correlated with the 'usual' ratios of the average concentrations. They show the sulfides of which metal form the more concentrated accumulations in an ore area.